(untitled) (Bangladesh Journal of Public Administration, 2022)
Outsourcing is the traditionally publicly provided services and recruitment of temporary or contractual employees. This process has become quite common in most industrialised nations. As Bangladesh is on its journey towards becoming a developed nation, a similar outsourcing initiative is visible in different government offices. Its importance has recently increased as outsourcing has moved from straightforward tasks to more complex and diversified tasks. Some academics of outsourcing claim that the promised high-quality service at a low cost consistently is yet to deliver. This paper aims to assess the quality and reliability aspects of services obtained from outsourcing staff and the effectiveness of the process in the context of the government sector of Bangladesh. Public Works Department (PWD) has been taken as a test case to conduct a survey and obtain experience-based views and feedback from the supervisory and managerial officers to assess service quality. This feedback, combined with the tender information from the e-GP portal, has been accumulated to get a brief account of outsourcing initiatives in the Government sector of Bangladesh and to perform an assessment of service quality from outsourcing staff.